English Teachers’ Strategies in Managing Large Classes: A Case Study - Lenny Marzulina; Dian Erlina; Muhammad Holandyah; Kasinyo Harto; Deta Desvitasari; Dessi Angreini (Indonesian Research Journal in Education |IRJE|, 2021)
This study aimed at finding (1) English teachers’ strategies in managing large classes, and (2) students’ perceptions towards their English teachers’ strategies. The design of this research is qualitative with a case study approach. This study involved four English teachers and ten students at one state Madrasah Tsanawiyah in Palembang, Indonesia. The data were collected through observations, interviews, and document review. Thematic analysis was conducted across a data set. The findings demonstrated that planning the lesson, organizing and controlling the students, managing classroom communication and talking time, then giving written and timely feedback on students’ works were the strategies applied by the English teachers. The use of these strategies was positively perceived by the students that they could have a better understanding, practice mutual-respect, and enjoy the lesson. Therefore, it might be a good idea to review teachers’ strategies in this study to address the difficulty of teaching English in large class settings.